MUNÃ‚SABÃ‚T AL-QURâ€™AN MENURUT AL-BIQÃ‚â€™I - Simanjuntak, Dahliati (IAIN Padangsidimpuan, 2018)
This article reviews about the al-Qur'anic munasabat according to al-Biqa'i in his interpretation. Considering that there are a lot of good looking sequences and structures related to verses and letters in the Qur'an as if there is no agreement with the verse or the letter before or after it. Al-Biqa 'I reviewed many of the al-Qur'anic munasabat in his book Nazhm al-Durar fî Tanasub al-Âyât wa al-Suwar at length..